Center the Relationship between Self-Leadership Behaviors of Sports-Sports Training Specialists and Job Satisfaction Levels (An Example from Eastern Anatolia Region) - Muhammed Bahadır Sandıkçı; Metin Yıldız; Abdurrahman Kırtepe (Journal of Educational Issues, 2024)
This study aims to determine the relationship between self-leadership behaviors and job satisfaction levels of Sports-Sports Training Specialists working in Provincial Directorates of Youth and Sports. The research population consists of 230 Sports-Sports Training Specialists working in the Provincial Directorates of Youth and Sports in the Eastern Anatolia Region. “Personal Information Form”, “Self-Leadership Questionnaire-SLQ” and “Job Satisfaction Scale” were used for data collection. 72.2% of the participants are male, 73.4% have an undergraduate degree and 64.6% are working in their institution on a contractual basis. There is a significant difference in favor of women between gender and the self-talk sub-dimension of the self-leadership scale. There was a significant difference between the working positions and the total score of the self-leadership scale and the sub-dimension of self-cueing in favor of permanent employees. There was a statistically significant difference between the job satisfaction scale and the sports training specialists having poor economic status. No positive relationship was found between self-leadership and job satisfaction. It has been concluded that female sports-sports training specialists are more focused on self-talk than males and this has an effect on self-leadership levels, but gender does not affect their job satisfaction levels. Permanent staff experts motivate themselves better and have a better sense of self-leadership than contracted experts. It has been determined that compared to their senior colleagues, newcomers to the profession are in an effort to reveal their self-leadership behaviors more in order to prove themselves in their institutions and to be successful.